Skrinning Fitokimia, Profil Spektrum Gugus Fungsi, dan Formuasi Sediaan Effervescent Limbah Batang Pisang Kepok - Purnama, Robby Candra; Primadiamanti, Annisa (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2020)
Kepok banana plants contain secondary metabolites such as tannins and flavonoids. Tannins and flavonoids have various properties for human health. Research has been carried out to identify secondary metabolite compounds (tannins, flavonoids, and saponins) by using the phytochemical screening method to see the functional group profile contained in the extract of kepok banana stem waste. Kepok banana stem waste was extracted in 96% ethanol, then evaporated and screened phytochemically. This extract was used to prepare effervescently. Screening results showed that tannin and flavonoids were identified by the appearance of the following color black-green and dark red, respectively. Meanwhile, saponins were negative because the foam formed had a height of 0.3 cm and did not meet the saponins' positive requirements (1-3 cm high foam and stable for 5 minutes). Identification of functional groups in the extract of kepok banana stem waste using Fourier-transform Infrared Spectroscopy (FTIR) showed that C-C stretching in the area 2927.24 cm-1, O-H stretching in the 3423.87 cm-1 area, C=O stretching in the 1648.87 cm-1 area. Also appeared bending CH2 in the region of 1421.45 cm-1, and C-C in the area of 1149.98 cm-1. The characteristics of three different formulas (A, B, and C) of effervescent have been investigated: the moisture content of 2.51%; 2.55%, and 2.52%, respectively. Then, flow rate of 8.81 g/s; 8.83 g/s; and 8.82 g/s, compressibility of 14.5%; 14.4%; and 14.5%, and a pH of 5.97; 5.98; and 5.97 respectively. All parameters are eligible.